PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA STAF KANTOR WILAYAH BADAN PERTANAHAN NASIONAL PROVINSI ACEH PROVINSI ACEH - Arfan, Rahmat (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The purpose of this paper is to find out how much influence work stress has on the performance of staff at the Regional Office of the Aceh Province National Land Agency. Then to find out how much influence work motivation has on the performance of staff at the Regional Office of the Aceh Province National Land Agency And find out how much influence work stress and work motivation have on the performance of staff at the Regional Office of the National Land Agency of Aceh Province. The methodology used in this paper is quantitative, with analysis carried out using reliability, validity, and multiple linear regression. With the conclusion that work stress has a negative and significant effect on performance, work motivation has a positive and significant effect on performance, and simultaneously, work stress and work motivation have a significant effect on the performance of the regional office staff of the Aceh provincial national land agency